Rett syndrome complicated by diabetes mellitus type 1 - Yasutaka Kuniyoshi; Satoru Takahashi (Endocrinology, Diabetes & Metabolism Case Reports)
Rett syndrome (RS) is an X-linked neurodevelopmental disorder primarily affecting females. RS and diabetes mellitus (DM) type 1 are rare disorders with distinct etiologies. Although some cases of RS complicated by DM type 1 have been reported, the association between these distinct conditions is poorly understood and warrants further studies to elucidate the underlying mechanisms and inform clinical management. We report the case of a 10-year-old girl diagnosed with RS and DM type 1. The patient initially presented at 3 years of age with polydipsia, polyuria and decreased appetite over several weeks. Physical examination showed signs of dehydration, and laboratory evaluation revealed hyperglycemia, elevated HbA1c, glycosuria, ketonuria and low C-peptide levels. Anti-glutamic acid decarboxylase antibodies were positive, confirming autoimmune DM type 1. Fluid resuscitation and insulin therapy were initiated with good glycemic control on continuous subcutaneous insulin infusion. A review of her history revealed normal early developmental milestones, including the onset of stereotypical hand movements at 3 years, communication impairment and seizures at 4 years and a diagnosis of autism spectrum disorder. At 10 years of age, genetic testing revealed a pathogenic MECP2 mutation. Clinical features, including breathing abnormalities, bruxism, abnormal tone and inappropriate laughing, met the diagnostic criteria for RS. This is the reported first case of RS with a confirmed MECP2 mutation complicated by DM type 1. Our case report contributes to the increasing evidence supporting the potential association between RS and DM type 1.